2017
DOI: 10.1002/iub.1645
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 expression and urinary HSP72 in relation to biomarkers of inflammation and oxidative stress in diabetic nephropathy patients

Abstract: Diabetic nephropathy (DN) is one of the major causes of end-stage renal disease. Nod-like receptors nucleotide-binding domain and leucine-rich repeat pyrin-3 domain (NLRP3) inflammasome displays a considerable role in the chronic inflammatory state observed in diabetic patients. Urinary heat shock protein 72 (uHSP72) is a sensitive and specific biomarker for the early detection of acute kidney injury. The aim of this study was to evaluate NLRP3 relative gene expression, its correlation with inflammatory and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…Therefore, HSPA/HSP70 may be beneficial in early DN because of its intracellular cytoprotective activity, but when albuminuria develops extracellular HSPA/HSP70 may contribute to the tubular-interstitial damage that is a key driver of DN progression. Consistent with this, a small study performed in patients with DM2 showed an association between urinary HSPA/HSP70 levels and albuminuria [ 112 ]. Moreover, serum HSPA/HSP70 levels were higher in DM2 patients with albuminuria [ 113 ] and polymorphisms of the HSPA/HSP70 gene were associated with DN in DM2 patients [ 114 ].…”
Section: Heat Shock Proteinssupporting
confidence: 68%
“…Therefore, HSPA/HSP70 may be beneficial in early DN because of its intracellular cytoprotective activity, but when albuminuria develops extracellular HSPA/HSP70 may contribute to the tubular-interstitial damage that is a key driver of DN progression. Consistent with this, a small study performed in patients with DM2 showed an association between urinary HSPA/HSP70 levels and albuminuria [ 112 ]. Moreover, serum HSPA/HSP70 levels were higher in DM2 patients with albuminuria [ 113 ] and polymorphisms of the HSPA/HSP70 gene were associated with DN in DM2 patients [ 114 ].…”
Section: Heat Shock Proteinssupporting
confidence: 68%
“…Similar results were obtained in diabetic mice where TLR4 deletion or HSP70 inhibition reduced albuminuria and markers of inflammation and tubular injury [92]. Further supporting these findings, patients with T2DM with albuminuria showed higher serum HSP70 levels [93] as well as an association between urinary HSP70 levels and albuminuria [94]. Serum HSP70 was also found to be higher in patients with diabetic retinopathy, together with HIF-1α compared with subjects without [95] and correlated well with asymmetric dimethylarginine (ADMA) and C-reactive protein (CRP) levels in T2DM patients compared with healthy controls [96].…”
Section: Hsp70supporting
confidence: 62%
“…A low nephron number, as induced here by early uninephrectomy, further aggravates hyperfunction, and accelerates the demise of the remnant nephrons (42). Several studies have documented an increased expression of NLRP3 inflammasome components in renal parenchymal cells in experimental and human DKD and hence speculated on a role of IL-1β in CKD progression (18, 4346). Indeed, Shahzad et al found db/db mice with T2DM to be protected from kidney disease by injecting human recombinant IL-1R antagonist anakinra (18).…”
Section: Discussionmentioning
confidence: 99%